2017
DOI: 10.1007/s41810-017-0015-z
|View full text |Cite
|
Sign up to set email alerts
|

Decay of High-Concentration Aerosol in a Chamber

Abstract: High-concentration aerosol is supposed to be crucial in some air pollution events. Aerosol always decays due to such mechanisms as coagulation, gravitational settling and diffusion deposition in a chamber; so its concentration needs to be calibrated in chamber experiments, especially for high-concentration aerosol. Two methods including the wall-loss correction and the direct simulation Monte Carlo (DSMC) were used to describe decay of the aerosol concentration. The parameters of diffusion deposition were fitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…In most studies, the agglomeration between particles and the effect of electrostatic interaction on the natural deposition of erosols were not considered. In other areas of research, Longbo Liu (Qiu et al, 2017) studied the effect of chamber erosol concentration on its natural settling. The results showed that when the erosol concentration was high and 10 4 /cm 3 , the agglomeration between the erosols must be considered.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, the agglomeration between particles and the effect of electrostatic interaction on the natural deposition of erosols were not considered. In other areas of research, Longbo Liu (Qiu et al, 2017) studied the effect of chamber erosol concentration on its natural settling. The results showed that when the erosol concentration was high and 10 4 /cm 3 , the agglomeration between the erosols must be considered.…”
Section: Introductionmentioning
confidence: 99%